Cover page - Boothman, Derek (International Gramsci Journal, 2023)
This is an abstract of the cover page of «International Gramsci Journal», vol. 4, No. 13 (Second Series- Seconda Serie), winter-inverno 2020. Photo: the Sardinian wooden cart that Gramsci sculpted for the Schucht sisters, Evgenija and Julija.